2017
DOI: 10.1074/jbc.m116.758508
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA LINC00672 contributes to p53 protein-mediated gene suppression and promotes endometrial cancer chemosensitivity

Abstract: Thousands of long intergenic non-protein coding RNAs (lincRNAs) have been identified in mammals in genome-wide sequencing studies. Some of these RNAs have been consistently conserved during the evolution of species and could presumably function in important biologic processes. Therefore, we measured the levels of 26 highly conserved lincRNAs in a total of 176 pairs of endometrial carcinoma (EC) and surrounding non-tumor tissues of two distinct Chinese populations. Here, we report that a lincRNA, , which posses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 54 publications
2
45
0
Order By: Relevance
“…However, there is a lack of similar investigations in NPC, and little is known about the influence of EBV infection on MALAT1. LINC00672 is a p53‐targeting lncRNA that strengthens the p53‐mediated suppression of LASP1 . In our study, LINC00672 was upregulated in EBV‐infected 293, GC, and NPC cells.…”
Section: Discussionsupporting
confidence: 52%
“…However, there is a lack of similar investigations in NPC, and little is known about the influence of EBV infection on MALAT1. LINC00672 is a p53‐targeting lncRNA that strengthens the p53‐mediated suppression of LASP1 . In our study, LINC00672 was upregulated in EBV‐infected 293, GC, and NPC cells.…”
Section: Discussionsupporting
confidence: 52%
“…Accumulating documents have revealed that lncRNAs play a critical role in tumorigenesis and can be used as biomarkers for diagnosis or prediction of survival and recurrence in multiple cancers (5)(6)(7)(8)(9). For instance, in 2017, Idogawa et al reported that long non-coding RNA NEAT1 was a transcriptional target of p53 and modulated p53-induced transactivation and tumor-suppressor function (10).…”
Section: Introductionmentioning
confidence: 99%
“…Several lncRNAs have been shown to express differently in EC tissues and are implicated in the biological processes related to malignant transformation and metastasis . However, these lncRNAs are concentrated on the autosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the long noncoding RNAs (lncRNAs) have been actively investigated, because they are involved in regulating various biological processes of malignant tumors, including EC . For example, lncRNA GAS5 acts as a tumor suppressor by inhibiting the expression of miR‐103 in EC, and LINC00672 cooperates with hnRNPs in p53‐mediated LASP1 suppression and promotes the chemosensitivity of EC cells . In addition, HOTAIR also plays an important role in the carcinogenesis of EC …”
Section: Introductionmentioning
confidence: 99%